Analisis Semiotika Roland Barthes dalam Novel Laut Bercerita Karya Leila S. Chudori - Rizki, Baiq Malinda Dwi; Mohzana; Ernawati, Titin (MODELING: Jurnal Program Studi PGMI, 2025)
This research, entitled “Semiotic Analysis of Roland Barthes in the Novel Laut Bercerita” by Leila S. Chudori, aims to identify signs in the novel and analyze their denotative, connotative, and mythical meanings based on Roland Barthes’s theory. The research method used was descriptive qualitative, using literature review techniques through intensive reading and recording quotations containing symbols. The results show that the novel Laut Bercerita contains signs that represent various aspects of socio-political life, such as betrayal, the struggles of the younger generation, education, gender, death, nature, and political repression. At the denotative level, the signs convey literal meaning; at the connotative level, they convey symbolic meaning related to emotional and social experiences. While at the mythical level, these signs form broader ideologies, such as the myth of the fragility of loyalty, the struggle of the younger generation as agents of change, a critique of patriarchy, sacrifice as a spirit of struggle, and the legitimacy of power through imprisonment. This study concludes that the novel Laut Bercerita is not only a literary work with aesthetic value, but also a medium for social and ideological criticism that revives the collective memory of the Indonesian nation.